2014
DOI: 10.4103/0973-1296.127345
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico studies on the anticancer and apoptosis-inducing activities of the sterols identified from the soft coral, subergorgia reticulata

Abstract: Background:Gorgonians and other octocorals are known to possess a huge array of secondary metabolites in which sterols are the major group of secondary metabolites apart from sesquiterpenes and diterpenes, and the bioactive metabolites could show marked biomedical potential for future drug discovery.Objective:This study was intended for the isolation and identification of sterols from the octocoral Subergorgia reticulata and to evaluate the anticancer and apoptosis-inducing activities of the identified sterols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…We were able to find several previous studies that discussed the anticancer potential of the compounds reported in the percentage study. Cholesta-5,22diene-3-ol, ergosta-5-22-dien-3-ol and cholest-5-en-3-ol, all isolated from the soft coral Subergorgia reticulate, have been reported to possess moderate anticancer potentials based on cytotoxicity studies in Dalton's lymphoma ascite cells (Byju, Anuradha, Vasundhara, Nair, & Kumar, 2014). Stigmasta-5,24(28)-dien-3-ol, isolated from Sargassum angustifolium has been reported to have potential anticancer activity in T47D and HT29 carcinoma cells with IC 50 values of 27.94 ± 9.3 and 70.41 ± 7.5 μg ml -1 respectively (Khanavi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We were able to find several previous studies that discussed the anticancer potential of the compounds reported in the percentage study. Cholesta-5,22diene-3-ol, ergosta-5-22-dien-3-ol and cholest-5-en-3-ol, all isolated from the soft coral Subergorgia reticulate, have been reported to possess moderate anticancer potentials based on cytotoxicity studies in Dalton's lymphoma ascite cells (Byju, Anuradha, Vasundhara, Nair, & Kumar, 2014). Stigmasta-5,24(28)-dien-3-ol, isolated from Sargassum angustifolium has been reported to have potential anticancer activity in T47D and HT29 carcinoma cells with IC 50 values of 27.94 ± 9.3 and 70.41 ± 7.5 μg ml -1 respectively (Khanavi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer activity of soft coral extracts has been previously reported. 34,35 For example, diterpenes from the soft coral Xenia elongata were found to induce apoptosis in a genetically engineered mouse cell line which was D3-deficient in the BAK1 and BAX genes. 35 The preliminary results of the current study therefore indicate the potential benefit of Sarcophyton sp.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the present findings for cytotoxic activity of compound 8 are consistent with results demonstrated for similar steroidal compounds obtained from various marine natural sources. [ 35 36 ] A previous study had shown that ergosta-5,24 (28)-dien-3-ol (8), reported from several Haliclona sponges, possess moderate cytotoxicity against the human foreskin fibroblast cell line (Hs27 cells) with an IC 50 value of 58 μM. [ 34 ] On the other hand, a recent study revealed that alkaloids, isolated from roots of Zanthoxylum nitidum, with mannopyranoside indole nucleus, possessed significant cytotoxic activities against selected tumor cell lines with IC 50 of <30 μm.…”
Section: Resultsmentioning
confidence: 99%